Distribution and harmfulness of the tuber nematode Ditylenchus destructor on domestic potato varieties - Sigareva, D.; Fedorenko, S.; Bondar, T.; Taktayev, B.; Tschigrin, N. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
A survey of 11 domestic potato varieties in 2017 and 2018 in the spring after storage showed that the infection of the tubers of Ditylenhus destructor Thorne, 1945 did not exceed 0.5—7% in them. This allowed us to classify the studied varieties as a relatively stable group. The loss of harvest during storage in 2017 was from 1.0 to 6.4%; in 2018 from 0 to 3.3%. The accounts tubers affected by the D. destructor in 7 blighty potato varieties during the harvest period (October 2016) and after storage (March 2017) allowed to determine the level of development of the disease and to classify Chervona Ruta, Yavor, Tiras to relatively stable varieties, Slavyanka and Teterev — to medium — and two varieties Serpanok and Svitanok kievskii — in the receptive.